56 The development of a mobile app to support the management of swallowing difficulties. (15th December 2021) - Ganeva, Teodora; Lin, Xing-Chan; Bassi, Daiana; Molyneux, Gemma; Fu, Yun; Halfpenny, Rhiannon
Abstract : Swallowing difficulties (dysphagia) are typically assessed using clinical and instrumental assessments, alongside the capture of a detailed case history. Patients and carers are often asked to recall details of the foods and drinks consumed, quantities, and difficulties experienced. Typically, clinical teams request this information on the spot, compromising the accuracy of information provided. In some instances, parents and carers keep paper-based mealtime diaries, but these are easily forgotten or lost. We have been investigating how technology can be used to support our patients and their carers to provide accurate information to clinical teams to support the management of their condition. With a growing patient desire for digitalised healthcare systems and an increasing number of young people with access to a mobile phone or tablet, transferring these traditionally paper-based health tools to a digital platform will help to streamline assessment and management processes, and improve patient outcomes and satisfaction. As part of a joint collaboration between GOSH and UCL Industry Exchange Network, the Speech and Language Therapy team developed a mobile app 'food-diary' to support the assessment and management of swallowing in young people. The app provides a tool for patients and carers to record information, through a structured system of questions, to provide clinically useful information about mealtimes and swallowing. In addition, the app delivers information on food consistencies, to support carers provide meals which are of a swallowing consistency recommended by the clinical team. We also include a patient story which describes the process of undergoing a Videofluoroscopy, to help patients and carers prepare for this clinical investigation. The app will be trialled with a small group of young people with dysphagia and/or their primary carers. Feedback from these trials will be used to secure funding to further develop the prototype.